HUBUNGAN ANTARA ASUPAN MAKANAN DAN STATUS KESADARAN GIZI KELUARGA DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS SEWON I, BANTUL - Purwaningrum, Sari; Wardani, Yuniar (Universitas Ahmad Dahlan, 2012)
Background: Poor nutritional status of children in Puskesmas Sewon I in 2007 amounted to 0.60%. Family Nutrition Awareness Status in Puskesmas Sewon I was at 47.06%. Average consumption of energy and protein adequacy of children under the minimum requirements is 19.8% to 9.9% for en-ergy and protein. Nutritional status is influenced by several factors, either directly or indirectly and purpose of this study was to determine the relationship of nutrition intake and family nutrition awareness status with under five years child nutritional status in Puskesmas Sewon I Bantul Yogya-karta. Method: Design of this research was cross sectional. The sample size of this study was 97 respon-dents. Sampling method of the study was proportional cluster random sampling technique. The variables examined in this research include under five years child nutritional status, nutrition intake, and fam-ily nutrition awareness status. The relationship of each variable was seen by using the Chi Square statistical test. Results: Results showed that of 97 respondents found 39 children (40.2%) had one and the nutri-tional status of 58 children (59.8%) had normal nutritional status. Bivariate analysis showed a relation-ship between under five years children nutritional status with food intake p < 0.05 (p = 0.000) and for under five years children nutritional status with family nutrition awareness status p < 0.05 (p = 0.03). Conclusion: There was a relationship of nutrition intake and family nutrition awareness status with under five years child nutritional status. Keyword: nutrition intake, family nutrition awareness status, under five years children nutritional status, Puskesmas Sewon